Respuesta :
let x be the age of ishaan so the age of ben will be 12+x. the equation will become x=x+12
Going 3 years back, the age of ishaan was x-3 so that of ben would be x+12-3 before 3 years. at that time the age of ben was 4 times the age of ishaan. it means x+12-3(the age of ben)=4(x-3(the age of ishaan))
solving this equation, we get the answer x=7. this is the age of ishaan in the present.
Going 3 years back, the age of ishaan was x-3 so that of ben would be x+12-3 before 3 years. at that time the age of ben was 4 times the age of ishaan. it means x+12-3(the age of ben)=4(x-3(the age of ishaan))
solving this equation, we get the answer x=7. this is the age of ishaan in the present.
х years - Ishaan
(x + 12) years - Ben
3 years ago :
(х - 3) years - Ishaan
((x + 12) - 3) years - Ben
-------------------------------------------------
(x + 12) - 3 = (x - 3) * 4
x + 9 = 4x - 12
x - 4x = - 12 - 9
- 3x = - 21
x = 21 : 3
х = 7 years - is Ishaan now.
(x + 12) years - Ben
3 years ago :
(х - 3) years - Ishaan
((x + 12) - 3) years - Ben
-------------------------------------------------
(x + 12) - 3 = (x - 3) * 4
x + 9 = 4x - 12
x - 4x = - 12 - 9
- 3x = - 21
x = 21 : 3
х = 7 years - is Ishaan now.